Linking phylogeography and recent dispersal in high mountains : Insights from two Iberian amphibians - Lucati, Federica (2021)
Unveiling how genetic diversity and structure of high mountain populations evolved and what factors are currently shaping it is crucial to predict how species will respond to threats such as climate change, and this will ultimately help to design species-specific conservation measures. Therefore, an integrative approach that combines the study of phylogeographic processes and contemporary dispersal dynamics is required to shed light on the mechanisms underlying spatial patterns of present-day genetic diversity and population structure, which can help to predict species responses to ongoing or future environmental changes. The general aim of this thesis was to uncover major historical and contemporary factors explaining the current genetic diversity and structure of selected Iberian amphibians living in high mountains, namely the Pyrenean brook newt, Calotriton asper, and the midwife toads of the Alytes obstetricans complex. I integrated various techniques, including genetic and mark-recapture analyses, to provide new insights into the phylogeographic history of the study species, describe the genetic consequences of chytridiomycosis outbreaks in midwife toads, inform on current connectivity in C. asper, and characterize its process of lake recolonization following invasive fish removal. Specifically, I showed that C. asper likely endured the last glaciation in five distinct glacial refugia across the Pyrenees, and I detected evidence of extensive mito-nuclear discordances and admixture between taxa of the A. obstetricans complex across three Iberian mountain ranges. A. obstetricans populations hit by a relatively recent chytridiomycosis outbreak had a reduced effective size and were depleted of genetic diversity. Finally, although I found that the majority of C. asper dispersal events involved geographically close populations, I also found potential for occasional long-distance dispersal and revealed the importance of neighbouring fishless areas as source of individuals for restored lakes. Overall, the results of this thesis contribute to improve our understanding of the factors responsible for species structuring in high mountains and may be useful to guide future management decisions for C. asper and the A. obstetricans complex.